Interpretation of Behaviour of DNA – Molecules by Quantum Mechanics - Rahmani, Shibli (International Journal of Computer Sciences and Engineering, 2025)
Through in early fifties Watson (a biologist) and crick (a physicist) published their (Nature, 1953) and proposing double helix model for the DNA structure but unwinding of the two strands remained a problem and is still unsolved. The major criticism against the double helix proposition is that the two chains will have to unwound in order to expose the bases, whose ordered sequences gives the genetic information, so that replication may occur and a new complementary strand may from. Now our submission is to take up the problem with quantum approach and we refer to the two faces of DNA structure, both of which are equally satisfactory pictures and we might guess that they should equal energies. But there should be certain amplitude that all the electrons can flip from one condition to the other shifting the position of the unfiled position to the opposite end. There are nevertheless, the usual two stationary states. |1> and | 2> which may be the sum of and difference combination of two base states 1> and 2>. The rate of flipping and therefore |A> should be sensitive to the complete structure of the molecule, then by changing A the energy might be splitting and hence frequency getting changed effecting the mating behaviour of the gamete. It is the behavioural phenomenon which we called mood of the gamete. Also the molecule therein does not have perfectly symmetrical. The same basic phenomenon should exist with slide modifications, even if there is some treatment slight asymmetries in the molecules could as well be introduced changing the mood. Still another feature of such a molecule is that in the two base states shown the centre of electronic charge is found to be located at different palaces thereby, giving evidence of influences due to subjective magnetic is electronic field. The DNA molecules have a quantum Mechanical behaviour and that flipping of the electronics are responsible for such behaviour.